Pemecahan Sertifikat Hak Milik Atas Tanah Perorangan Lebih dari 5 (Lima) Bidang di Desa Babakancaringin Cianjur dalam Terwujudnya Kepastian Hukum - Syah Abdul Ghani; Lina Jamilah (Bandung Conference Series: Law Studies, 2024)
Abstract .The process of splitzing land ownership certificates is regulated in the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Service Standards and Land Regulations. In practice, the application process for splitzing the certificate of ownership of individual land more than 5 (five) fields in Babakancaringin Cianjur Village is accepted by the Cianjur Regency Land Office. This research aims to find out the process of splitzing the certificate of ownership of individual land more than 5 (five) fields in Babakancaringin Cianjur Village is in accordance with the applicable provisions and to find out the legal protection for land buyers against the split certificate of ownership of individual land more than 5 (five) fields in Babakancaringin Cianjur Village in the realization of legal certainty. The research method used in this research is the normative juridical approach method. Research specification is descriptive analytical. The research stage was carried out by conducting library research and interviews as supporting material for secondary data and data analysis was carried out using qualitative juridical methods. The results of this study found that the process of splitzing the Certificate of Ownership on individual land in Babakancaringin Cianjur Village is not in accordance with the applicable provisions, which are contained in the Regulation of the Minister of Agrarian Affairs / Head of BPN of the Republic of Indonesia Number 1 of 2010 concerning Service Standards and Land Regulations in Appendix II concerning the Split / Separation of Individual Land Fields and Legal Entities. In addition, Legal Protection for land buyers in Babakancaringin Cianjur Village is the provision of Land Ownership Certificates in the realization of legal certainty. ABSTRAK. Proses pemecahan Sertifikat Hak Milik atas tanah diatur dalam Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 1 Tahun 2010 tentang Standar Pelayanan dan Pengaturan Pertanahan. Dalam praktik proses permohonan pemecahan Sertifikat Hak Milik atas tanah perorangan lebih dari 5 (lima) bidang di Desa Babakancaringin Cianjur diterima oleh Kantor Pertanahan Kabupaten Cianjur. Penelitian ini bertujuan untuk mengetahui proses pemecahan Sertifikat Hak Milik atas tanah perorangan lebih dari 5 (lima) bidang di Desa Babakancaringin Cianjur sudah sesuai dengan ketentuan yang berlaku dan untuk mengetahui perlindungan hukum bagi pembeli tanah terhadap pemecahan sertifikat Hak Milik atas tanah perorangan lebih dari 5 (lima) bidang di Desa Babakancaringin Cianjur dalam terwujudnya kepastian hukum. Metode penelitian yang digunakan metode yuridis normatif. Spesifikasi Penelitian yang digunakan deskriptif analitis. Tahap penelitian dilakukan dengan melakukan penelitian kepustakaan dan wawancara, analisis data menggunakan metode yuridis kualitatif. Hasil dari penelitian bahwa Proses pemecahan Sertifikat Hak Milik atas tanah perorangan di Desa Babakancaringin Cianjur tidak sesuai ketentuan yang berlaku, yang terdapat dalam Peraturan Menteri Agraria/Kepala BPN Republik Indonesia Nomor 1 Tahun 2010 tentang Standar Pelayanan dan Pengaturan Pertanahan Lampiran II tentang Pemecahan/Pemisahan Bidang Tanah Perorangan dan Badan Hukum. Selain itu, Perlindungan Hukum bagi pembeli tanah di Desa Babakancaringin Cianjur adalah pemberian Sertifikat Hak Milik atas tanah dalam terwujudnya kepastian hukum.